2016
DOI: 10.5194/isprs-archives-xli-b3-447-2016
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Classification From Full-Waveform Lidar Data Based on Support Vector Machines

Abstract: ABSTRACT:In this study, a land cover classification method based on multi-class Support Vector Machines (SVM) is presented to predict the types of land cover in Miyun area. The obtained backscattered full-waveforms were processed following a workflow of waveform pre-processing, waveform decomposition and feature extraction. The extracted features, which consist of distance, intensity, Full Width at Half Maximum (FWHM) and back scattering cross-section, were corrected and used as attributes for training data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In this article, the RF classifier is demonstrated under the complex environments. We also compared its performance with the other classifiers, for example, linear-SVM and radial basis function SVM (RBF-SVM) [53], LR [54], KNN [55], and NB [56]. And the quantitative analysis is also evaluated.…”
Section: B Classification Based On Waveform Featuresmentioning
confidence: 99%
“…In this article, the RF classifier is demonstrated under the complex environments. We also compared its performance with the other classifiers, for example, linear-SVM and radial basis function SVM (RBF-SVM) [53], LR [54], KNN [55], and NB [56]. And the quantitative analysis is also evaluated.…”
Section: B Classification Based On Waveform Featuresmentioning
confidence: 99%
“…Close distances between multiple targets will cause echo overlap so deconvolution and multi-Gaussian fitting need to be used before feature extraction [12,13]. After the decomposition of echoes into multiple Gaussian components, the manual features combined with the support vector machine (SVM) [6] and random forest (RF) [14,15] methods can be used for classification. However, the accuracy is mainly subject to the quality of the manual features, which requires specialized knowledge.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, a combination of artificial features and machine learning can be used for land cover classification [2] and ocean engineering [3][4][5]. However, such algorithms are extremely dependent on a large number of manual features and annotation data [6] so the universality of those algorithms is limited.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a rule-based algorithm was used for classification tasks [2,36]. Other methods are based on classic machine learning that uses handcrafted features, such as nonlinear classification and support vector machine (SVM) classifiers [24], which have been widely used with point cloud classification tasks using handcrafted features from full-waveform LiDAR data [6,7,14,23,54]. Furthermore, for land-use classification tasks, Wang et al [37] demonstrated the importance of spatial distributional and handcrafted features of waveforms.…”
Section: Full-waveform Lidar Data Analysismentioning
confidence: 99%